Metacercárias de Austrodiplostomum compactum (Digenea: Diplostomidae) em Schizodon intermedius (Characiformes: Anostomidade) do reservatório de Jurumirim, Brasil - Ramos, Igor Paiva [UNESP]; Franceschini, Lidiane [UNESP]; Zago, Aline Cristina [UNESP]; Zica, Érica De Oliveira Penha [UNESP]; Wunderlich, Alison Carlos [UNESP]; De Lima, Felipe Pontieri [UNESP]; Da Silva, Reinaldo José [UNESP] (FapUNIFESP (SciELO), 2016)
This study reports the occurrence of Austrodiplostomum compactum metacercariae in the freshwater fish Schizodon intermedius (ximborê/piava) from a Neotropical reservoir in the Paranapanema River, state of São Paulo, Brazil. From a total of 75 fish collected, we found 38 infected with A. compactum metacercariae (prevalence = 50.67%) in the eyes. The mean intensity of infection and mean abundance were 9.05 ± 4.26 (1-155) and 4.59 ± 2.20 (0-155), respectively. Poulin’s Discrepancy Index was 0.87 and four specimens presented more than 10 metacercariae in their eyes. No correlation was observed between parasite abundance and standard length, total weight and condition factor (p>0.05). These metacercariae are reported for the first time in S. intermedius.
Austrodiplostomum compactum metacercariae (Digenea: Diplostomidae) in schizodon intermedius (Characiformes: Anostomidae) from Jurumirim reservoir, Brazil
Keywords: Eyefluke; Freshwater fish; Paranapanema River; Paraná River basin; Ximborê